A comprehensive approach to passive design strategies for public hospital / Jamaludin Muhamad, Hayroman Ahmad and Azhan Abdul Aziz - Muhamad, Jamaludin; Ahmad, Hayroman; Abdul Aziz, Azhan (2019)
Passive design is an element utilized from natural sources intended to maintain the comfort of the building's occupants. This source consists of natural lighting and ventilation adapted through openings in buildings. Building orientation is essential for design openings to be optimized more efficiently. However, occupants usually respond to their immediate environment to achieve the comfort and convenience of their space. The literature is reviewed to identify design strategies for passive design in order to enhance energy efficiency. This paper relates on energy efficiency strategies through passive design in which designers have systematic guidelines for the initial stages of public hospital design. Sustainable hospital architecture can be created through criteria derived from the information found in helping pre-process designers design public hospitals more efficiently in terms of energy use